Myosteatosis predicts higher complications and reduced overall survival following radical oesophageal and gastric cancer surgery. Issue 9 (September 2021) - Murnane, Lisa C.; Forsyth, Adrienne K.; Koukounaras, Jim; Pilgrim, Charles HC.; Shaw, Kalai; Brown, Wendy A.; Mourtzakis, Marina; Tierney, Audrey C.; Burton, Paul R.
Abstract: Introduction: Low muscle attenuation, as governed by increased intramuscular fat infiltration (myosteatosis), may associate with adverse surgical outcomes. We aimed to determine whether myosteatosis is associated with an increased risk of postoperative complications and reduced long-term survival after oesophago-gastric (OG) cancer surgery. Methods: Patients who underwent radical OG cancer surgery with preoperative abdominal computed tomography (CT) imaging were included. Myosteatosis was evaluated using previously defined cut-points for low skeletal muscle attenuation measured by CT. Oncological, surgical, complications, and outcome data were obtained from a prospective database. Results: Of 108 patients, 56% ( n = 61) had myosteatosis. Patients with myosteatosis were older (69.1 ± 9.1 vs. 62.8 ± 9.8 years, p = 0.001) and had a similar body mass index (BMI) (23.4 ± 5.3 vs. 25.9 ± 6.7 kg/m 2, p = 0.766) compared to patients with normal muscle attenuation. Patients with myosteatosis had a higher rate of anastomotic leaks (15% vs. 2%, p = 0.041). On multivariate analysis, myosteatosis was an independent predictor of overall (OR 3.03, 95% CI 1.31–6.99, p = 0.009) and severe complications (OR 4.33, 95% CI 1.26–14.9, p = 0.020). Patients with myosteatosis had reduced 5 year overall (54.1% vs. 83%, p = 0.004) and disease-free (55.2% vs. 87.2%, p = 0.007) survival. Conclusion: Myosteatosis is associated with a significantly increased risk of overall and severe complications as well as substantially reduced long-term survival. Assessment of muscle attenuation provides analysis beyond standard anthropometrics and may form part of preoperative physiological staging tools used to improve surgical outcomes.